Transition-Metal-Free Synthesis of Trifluoromethylated Furans via a Bu3P-Mediated Tandem Acylation–Wittig Reaction - Li, Maizhan; Zhou, Wei (Synlett, 2020)
A highly efficient nucleophilic addition–O-acylation–intramolecular Wittig reaction of β-trifluoromethyl α,β-enones is disclosed. This strategy features mild reaction conditions and provides a practical transition-metal-free method to a set of biologically significant trifluoromethylated furans in high yields with diverse functional groups.
Keywords: β-trifluoromethyl α,β-enones; Wittig reaction; nucleophilic addition; furans; trifluoromethylated furans